2018
DOI: 10.3390/molecules23020265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on the Renin-Angiotensin-Aldosterone System in l-NAME-Induced Hypertension

Abstract: The renin-angiotensin-aldosterone system (RAAS) is a dominant player in several cardiovascular pathologies. This study investigated whether alterations induced by l-NAME, (NLG)-nitro-l-arginine methyl ester, a nitric oxide synthase inhibitor, and the protective effect of melatonin are associated with changes in the RAAS. Four groups of 3-month-old male Wistar rats (n = 10) were treated as follows for four weeks: untreated controls, rats treated with melatonin (10 mg/kg/day), rats treated with l-NAME (40 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 78 publications
5
41
0
3
Order By: Relevance
“…In fact, angiotensin II is able to activate the NADPH oxidase enzyme leading to an increase in intracellular superoxide anion (O -2 ) formation; this anion functions in the brain as a powerful cellular signaling mechanism leading to sympathoexcitation (Oliveira-Sales et al, 2009;Collister et al, 2016). In contrast, recently it was reported that L-NAME-induced hypertension is not dependent on increased Angiotensin II levels (Simko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, angiotensin II is able to activate the NADPH oxidase enzyme leading to an increase in intracellular superoxide anion (O -2 ) formation; this anion functions in the brain as a powerful cellular signaling mechanism leading to sympathoexcitation (Oliveira-Sales et al, 2009;Collister et al, 2016). In contrast, recently it was reported that L-NAME-induced hypertension is not dependent on increased Angiotensin II levels (Simko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…7 The l-NAME model of hypertension was chosen on the basis of our extensive experience with this model. [8][9][10][11] Moreover, this hypertension model seems to have several advantages: it is well standardized by appropriate dosing of l-NAME, and it is based on endothelial dysfunction with reduced NO production and complex neurohumoral activation; thus, it mimics, in certain respects, the essential hypertension in humans. 12 This experiment was considered to be a pilot study aimed to show the circadian BP and HR changes and to reveal the potential BP and HR dip in l-NAME-induced hypertension in rats.…”
mentioning
confidence: 99%
“…In patients with hypertension, the changes of these humoral factors may be the pathological basis of abnormal blood pressure rhythm. Previous studies have shown that melatonin can reduce blood pressure by affecting vascular endothelial system and RAAS system [24,25], but the mechanism is not completely clear. In this study, the stress-induced hypertension rat model was adopted to observe the antihypertensive effect of melatonin, and the central antihypertensive mechanism and target of melatonin were explored based on the neuroinflammation triggered by M1 polarization of microglia cells, providing experimental basis for further clarifying the mechanism of melatonin's involvement in regulating blood pressure.…”
Section: Discussionmentioning
confidence: 97%